Search for new light gauge bosons in Higgs boson decays to four-lepton final states in pp collisions at s√=8 TeV with the ATLAS detector at the LHC - Aad, G. (2015)
This paper presents a search for Higgs bosons decaying to four leptons, either electrons or muons, via one or two light exotic gauge bosons Zd, H → ZZd → 4l or H → ZdZd → 4l. The search was performed using pp collision data corresponding to an integrated luminosity of about 20 fb−1 at the center-of-mass energy of ffiffi s p ¼ 8 TeV recorded with the ATLAS detector at the Large Hadron Collider. The observed data are well described by the Standard Model prediction. Upper bounds on the branching ratio of H → ZZd → 4l and on the kinetic mixing parameter between the Zd and the Standard Model hypercharge gauge boson are set in the range ð1–9Þ × 10−5 and ð4–17Þ × 10−2 respectively, at 95% confidence level assuming the Standard Model branching ratio of H → ZZ → 4l, for Zd masses between 15 and 55 GeV. Upper bounds on the effective mass mixing parameter between the Z and the Zd are also set using the branching ratio limits in the H → ZZd → 4l search, and are in the range ð1.5–8.7Þ × 10−4 for 15 < mZd < 35 GeV. Upper bounds on the branching ratio of H → ZdZd → 4l and on the Higgs portal coupling parameter, controlling the strength of the coupling of the Higgs boson to dark vector bosons are set in the range ð2–3Þ × 10−5 and ð1–10Þ × 10−4 respectively, at 95% confidence level assuming the Standard Model Higgs boson production cross sections, for Zd masses between 15 and 60 GeV.